A Focus Group Study of Palliative Physician and Consultation-Liaison Psychiatrist Perceptions of Dealing with Depression in the Dying. Issue 4 (October 2022) - Lee, Wei; DiGiacomo, Michelle; Draper, Brian; Agar, Meera R.; Currow, David C.
Objective: To ascertain palliative physicians' and consultation-liaison psychiatrists' perceptions of depression care processes in patients with very poor prognoses, exploring key challenges and postulating solutions.Methods: A qualitative focus group study involving three 1-h online focus groups (2 palliative medicine and 1 psychiatry) were conducted between November-December 2020. Fellows and trainees were recruited from Australian and New Zealand Society of Palliative Medicine (n  =  11) and Royal Australian and New Zealand College of Psychiatrists (n  =  4). Data underwent conventional qualitative content analysis.Results: Participants perceived depression care to be complex and challenging. Perceived barriers included: inadequate palliative care psychiatry skills with variation in clinical approaches; lack of supportive health infrastructure (poor access to required interventions and suboptimal linkage between palliative care and psychiatry); lack of research support; and societal stigma. Suggested solutions included integrating care processes between palliative care and psychiatry to improve clinician training, establish supportive health systems and promote innovative research designs.Conclusions: Developing clinician training, supportive health systems and innovative research strategies centering on integrating palliative care and psychiatry care processes may be integral to optimising depression care when providing care to people with very poor prognoses.